Power-up control techniques for reliable SRAM PUF - Lee, Juyun; Jee, Dong Woo; Jeon, Dongsuk (IEICE Electronics Express, 2019)
Physically unclonable function (PUF) is a widely used hardware- level identification method. SRAM PUFs are the most well-known PUF topology, but they typically suffer from low reproducibility due to non-deterministic behaviors and noise during power-up process. In this work, we propose two power-up control techniques that effectively improve reproducibility of the SRAM PUFs. The techniques reduce undesirable bit flipping during evaluation by controlling either evaluation region or power supply ramp-up speed. Measurement results from the 180nm test chip confirm that native unstable bits (NUBs) are reduced by 54.87% and bit error rate (BER) decreases by 55.05% while reproducibility increases by 2.2×.
Keywords: Bit flipping; Control techniques; Deterministic behavior; Identification method; Physically unclonable functions; Power supply; Reproducibilities; Test chips; Physically unclonable function; Power-up control; SRAM